Myeloablative busulfan/cytoxan conditioning versus reduced-intensity fludarabine/melphalan conditioning for allogeneic hematopoietic stem cell transplant in patients with acute myelogenous leukemia. Issue 4 (3rd April 2018) - Dhere, Vishal; Edelman, Scott; Waller, Edmund K.; Langston, Amelia; Graiser, Michael; Connolly, Erin C.; Switchenko, Jeffrey M.; Esiashvili, Natia; Khan, Mohammad K.
Abstract: Fludarabine and melphalan (Flu/Mel) has emerged as a more tolerable chemotherapy-based conditioning regimen compared with busulfan and cyclophosphamide (Bu/Cy) for allogeneic stem cell transplant (allo-hematopoietic stem cell transplantation (HSCT)) patients with acute myelogenous leukemia (AML). We conducted a retrospective review of a single-institution database including patients with AML who received allo-HSCT following conditioning with Mel/Flu or Bu/Cy-based regimens. We performed descriptive statistical analysis to examine patient demographics and clinical outcomes. We identified 156 patients meeting criteria between 2005 and 2014. Overall, patients conditioned with Bu/Cy were significantly younger, but more likely to be treated in an earlier era than those receiving Flu/Mel. Regimen choice was not associated with relapse rates (RR), relapse-free survival (RFS), or overall survival (OS) on both univariate and multivariable analyses. Bu/Cy was associated with increased non-relapse mortality (NRM) on multivariable analysis. These findings demonstrate that Flu/Mel provides non-inferior disease control and could be an appropriate regimen for selected patients.